Social determinants of health in non-communicable diseases prevention policies in South Africa - Richard M. Rasesemola; Rose M. Mmusi-Phetoe; Yolanda Havenga (AOSIS, 2023)
Background: The South African government has developed many policies for the prevention and control of non-communicable diseases. However, non-communicable diseases remain among the major causes of morbidity and mortality in South Africa. Although these diseases are linked to interaction of multiple risk factors, many of which are modifiable, they continue to cause much suffering particularly among the marginalised and people from the lower socio-economic status. Objectives: The objective of this research was to explore and present the inclusion of social determinants of health in the policies meant for the prevention and control of non-communicable diseases in South Africa. Method: The qualitative document analysis approach was used to conduct policy analysis of purposefully selected policies for prevention and control of cancers, obesity and mental and behavioural disorders in South Africa. Results: The analysis revealed that policies for prevention and control of cancers, obesity and mental and behavioural disorders included policy intervention activities that focused on five social determinants of health: (1) governance, (2) social policies, (3) public policies, (4) material circumstances and (5) health system. Conclusion: Excluding most of the important social determinants of health in the policies for prevention and control of non-communicable diseases means that these policies would continue to fail in preventing these diseases from the root causes. Contribution: This article points out weaknesses in the policies meant for prevention and control of obesity, cancers and mental and behavioural disorders. This article further suggests policy improvement strategies that may be considered to effectively address these diseases.